Transformative community-engaged science: Strengthening relationships between science and society - Rajul E. Pandya; Amanda D. Boyd; Mónica I. Feliú-Mójer; Itzhak Yanovitzky (Proceedings of the National Academy of Sciences, 2025)
There is a critical need to strengthen science–society relationships—especially with historically marginalized communities—if we are to better and more equitably manage complicated, intertwined, global challenges at the intersection of environment, health, equity, and well-being. Community-engaged science, which focuses on shared leadership and mutual benefit in scientific partnership with communities, has the potential to transform science, communities, and even society. Despite this promise, however, community-engaged science is not always transformative. Presentations and discussions at the 5th National Academies Science Communication Colloquium demonstrated the importance of creating structures, practices, and a culture of science engagement that prioritizes listening and learning from communities. Based on presentations at the colloquium, research publications, and our own experiences, we share a set of evidence-informed principles that are common to successful community-engaged science across many contexts: respect, humility, listening, reciprocity, mutuality, and reflexivity. We also offer steps the scientific community can take to advance and improve the transformative practice of community-engaged science as part of a productive ecosystem of scientific activities: evolving norms and culture, integrating community science into current systems, building incentives and structures to support community-engaged science, developing a workforce skilled in community engagement, and investing in a coordinated research-to-practice agenda.